Development of a methodological framework of the process of verification and validation of software for small and medium enterprises - Grados Aguirre, Lizette (2015)
Today it is difficult for an SME to apply the Quality Models and proposed tests such as CMMI, TMMi,, TMap, IEEE Standard referring to the process of V & V, this primarily by: 1) the degree of complexity,; 2) cost constraints that SMEs do not have enough money to hire market specialists that can provide the directives they need or 3) simply because of the ignorance that exists about the benefits obtained. The present research has as main objective to develop a methodological framework Process Verification and Validation adjusted for socioeconomic reality of SME. The framework was applied to the project Inventory Control System of the Company QBOSS SAC, the initial situation of the company was analyzed, then the methodological framework developed was applied, and finally the results were positive for the organization.